Analysis of Environmental Factors and Parenting of Pregnant Women on the Development of Stunted Children (Oshada, 2025)
Stunting is a chronic nutritional problem influenced by environmental factors and parenting patterns starting during pregnancy. This study aims to analyze the relationship between environmental factors and maternal parenting patterns and the incidence of stunting in children in Gunungkidul Regency. This quantitative study used a case-control design with a sample of 210 mothers with children aged 24–59 months. Data were collected through structured interviews, home observations, and medical records of pregnancy examinations. The variables studied included antenatal care (ANC) compliance, home sanitation, nutritional intake during pregnancy, housing density, and access to clean water. Data analysis was performed using the Chi-Square test and logistic regression with a significance level of p